Kepemimpinan Geuchik dalam Meningkatkan pembangunan gampong Alue Krueng Kecamatan Pasie Raya Kabupaten Aceh Jaya(Studi Kepemimpinan Geuchik Miswar dalam pemgelolaan dana gampong) - darwin darwin; effendi hasan (Jurnal Ilmiah Mahasiswa Fakultas Ilmu Sosial & Ilmu Politik, 2018)
ABSTRACT Leadership of a headman (Geuchik) basically refers to how to coordinate the whole needs of people in every decision-making process. Geuchik should also be able to set targets to achieve for society development as well as communicate and channel their aspirations. It is also expected that a Geuchik be able to provide all the needs of the people living in his area. Funding provided by central government for village named dana gampong is very pivotal in speeding up the area development. Miswar, as a Geuchik, was expected to do the same thing. He should be able to actualize the accelerated development. The objective of this research was to know the process of village’s development under the rule of Miswar and to know the benefits gained from dana gampong in Alue Kareng in realizing speed up development.This study employed qualitative descriptive approach. The data were obtained from field and library study. Field study was performed by interviewing informants. Library study, on the other hand, was done by reading books, scripts, journals, rules, and other related references. The results showed that Miswar as a Geuchik always focus on situational, consultative leadership styles. He managed to do all of his duties successfully and well. His success can be seen from the main road reconstruction in several places. Dana Gampong benefited people in Alue Krueng by which road construction that gives easier access for people to travel to their plantation and rice fields. Geuchik Miswar is expected to develop his leadership skills and maintain his working spirit in order to speed up the process of achieving prosperity in Alue Krueng. It is also suggested that Geuchik Miswar and his staff optimally focus on making decision for public service so that the society can be more satisfied with the leadership skills possessed by their leader. . Keywords: Leadership, Development of Hope, Dana Gampong.